Digital Finance: Financial Recording Education for Women Entrepreneurs - Fifi Nurafifah Ibrahim; Sutiawati Sutiawati; St Nursanti Iskandar; Rina Rina (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This community service activity aims to improve literacy and digital-based financial recording skills among women entrepreneurs in Padanglampe Village, especially Family Welfare Empowerment (PKK) members who still rely on manual recording. The program is designed to provide ongoing education, introduce relevant digital finance applications, and offer assistance and consultation on their use. Research Design and Methodology: The activities were conducted through presentations on basic accounting materials, training on digital financial recording, demonstrations of the BukuWarung application and similar applications, and interactive discussion sessions. The approach used was socialization, hands-on practice, and participatory mentoring, actively involving partners throughout the entire process. Findings and Discussion: The results of the activity showed an increase in partners' knowledge of digital financial recording concepts and ease of use of smartphone-based financial recording applications. Partners also gained a greater understanding of basic accounting and financial recording, and a greater awareness of the importance of consistent financial recording. The participants' enthusiasm was evident in their active involvement in question-and-answer sessions, discussions, and the practical use of the application. Implications: This activity provides practical benefits for women entrepreneurs, especially in improving the efficiency of digital-based business financial management. The program also opens up opportunities for developing basic accounting consulting services and sustainable digital recording for rural communities.